(untitled) (Revista Apotheke, 2025)
This article presents a case study on the insertion of people with physical and intellectual disabilities in visual arts classes, based on experiences with painting. I use the theory of Vigotski (2007, 2011, 2021), which presents the development of people with disability through alternative ways activated by the senses that are not compromised by limitations. Thus, a concept used in this theory is compensation, understood as a factor of construction of subjectivity, which seeks, through the will to belong, to create unique forms of communication, expression and social insertion. Dewey (2010) is an author who also substantiates this study based on his considerations about experience as a continuity of life, in which art materializes as a subjective expression. As results, I present considerations about the paths that can be followed in visual arts classes, through pictorial language, to develop expressive processes for students with disabilities, concluding that painting is a process that mobilizes subjectivity in a unique, experiential and powerful way for the construction of alternative ways of expressing human personality.